Cystic Endometrial/ Glandular Hyperplasia.in Rabbit: A Case Study - DAS, G K; RISAM, K S (The Indian Journal of Animal Reproduction, 2023)
Present communication· records the incidence of cystic endometrial I glandular hyperplasia in a NewZealand W.h ite rabbit from sub-temperate climatic region of India.
Keywords: Rabbit; Cystic endometrium; Glandular Hyperplasia